Patients with advanced chronic kidney disease and vascular calcification have a large hydrodynamic radius of secondary calciprotein particles. Issue 6 (16th May 2018) - Chen, Wei; Anokhina, Viktoriya; Dieudonne, Gregory; Abramowitz, Matthew K; Kashyap, Randeep; Yan, Chen; Wu, Tong Tong; de Mesy Bentley, Karen L; Miller, Benjamin L; Bushinsky, David A
Abstract: Background: The size of secondary calciprotein particles (CPP2) and the speed of transformation (T50 ) from primary calciprotein particles (CPP1) to CPP2 in serum may be associated with vascular calcification (VC) in patients with chronic kidney disease (CKD). Methods: We developed a high throughput, microplate-based assay using dynamic light scattering (DLS) to measure the transformation of CPP1 to CPP2, hydrodynamic radius (Rh ) of CPP1 and CPP2, T50 and aggregation of CPP2. We used this DLS assay to test the hypothesis that a large Rh of CPP2 and/or a fast T50 are associated with VC in 45 participants with CKD Stages 4–5 (22 without VC and 23 with VC) and 17 healthy volunteers (HV). VC was defined as a Kauppila score >6 or an Adragao score ≥3. Results: CKD participants with VC had larger cumulants Rh of CPP2 {370 nm [interquartile range (IQR) 272–566]} compared with CKD participants without VC [212 nm (IQR 169–315)] and compared with HV [168 nm (IQR 145–352), P < 0.01 for each]. More CPP2 were in aggregates in CKD participants with VC than those without VC (70% versus 36%). The odds of having VC increased by 9% with every 10 nm increase in the Rh of CPP2, after adjusting for age, diabetes, serum calcium and phosphate [odds ratio 1.09, 95% confidence interval (CI) 1.03, 1.16, P = 0.005]. The area under the receiver operating characteristic curve for VC of CPP2 size was 0.75 (95% CI 0.60, 0.90). T50 was similar in CKD participants with and without VC, although both groups had a lower T50 than HV. Conclusions: Rh of CPP2, but not T50, is independently associated with VC in patients with CKD Stages 4–5.